2012
DOI: 10.1161/circinterventions.111.967596
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With OPN-305, a Humanized Anti–Toll-Like Receptor-2 Antibody, Reduces Myocardial Ischemia/Reperfusion Injury in Pigs

Abstract: Background-Toll-like receptor (TLR)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 34 publications
(47 reference statements)
0
67
0
Order By: Relevance
“…More recently, it was reported that inhibition of TLR2 with T2.5 protected against angiotensin II-induced cardiac fibrosis by attenuating macrophage recruitment and the inflammatory response in the heart. The humanized anti-TLR2 monoclonal antibody OPN305 has shown promising results for the prevention of myocardial ischemia/reperfusion injury (Arslan et al, 2012). OPN305 is able to block both TLR2/1-and TLR2/6-mediated signaling, reducing TLR2-mediated proinflammatory cytokine production.…”
Section: A Toll-like Receptor Signaling Inhibitionmentioning
confidence: 99%
“…More recently, it was reported that inhibition of TLR2 with T2.5 protected against angiotensin II-induced cardiac fibrosis by attenuating macrophage recruitment and the inflammatory response in the heart. The humanized anti-TLR2 monoclonal antibody OPN305 has shown promising results for the prevention of myocardial ischemia/reperfusion injury (Arslan et al, 2012). OPN305 is able to block both TLR2/1-and TLR2/6-mediated signaling, reducing TLR2-mediated proinflammatory cytokine production.…”
Section: A Toll-like Receptor Signaling Inhibitionmentioning
confidence: 99%
“…Dysregulated TLR2 signaling has been implicated in numerous diseases (e.g., sepsis, atherosclerosis, tumor metastasis, ischemia/reperfusion injury) (11)(12)(13)(14). Several inhibitors of TLR2 signaling have been developed (15)(16)(17)(18)), yet none is licensed for human use. A better understanding of the Toll/IL-1 receptor resistance (TIR) domain interactions involved in TLR2 signaling could lead to novel therapeutic agents.…”
mentioning
confidence: 99%
“…For example OPN-301, a novel anti-TLR2 monoclonal antibody, was shown to reduce infarct size and preserve cardiac function and geometry when administered before reperfusion in a mouse MI model [34]. Importantly, the same group recently reported development of a clinical-grade humanised anti-TLR2 antibody (OPN-305) and showed similar benefit in pigs after myocardial ischemia/reperfusion injury [153]. These data suggest that OPN-305 may have potential as an adjunctive for reperfusion therapy in MI patients.…”
Section: Therapeutic Approaches To Target Damp Pathwaysmentioning
confidence: 99%